Magnitude of immediate postpartum anaemia and associated factors among mothers at selected public hospitals in North Shoa Zone, Oromia regional state, Ethiopia: a cross-sectional study in 2022 - Genanew Nigusu; Negash Wakgari; Mistiwat Abebe; Meseret Moroda (BMJ Open)
Background Anaemia is a worldwide public health problem affecting over 800 million reproductive-age women. In developing countries, postpartum anaemia is a significant cause of maternal morbidity and mortality. In Ethiopia, postpartum anaemia remains a public health issue.Objective To assess the magnitude of immediate postpartum anaemia and associated factors among postpartum mothers who delivered at public hospitals in the North Shoa Zone, Oromia regional state, Ethiopia, in 2022.Design A cross-sectional study was conducted. A systematic random sampling method was used to select study participants. Data were collected using Kobo Collect software and exported to the Statistical Package for the Social Sciences (SPSS) version 26 for analysis. Bivariable and multivariable logistic regression analyses were performed to examine associations between variables. Statistical significance was declared at a p-value of <0.05, and the adjusted odds ratio (AOR) with a 95% CI was used to determine the strength of associations.Setting A facility based at three public hospitals in the North Shoa Zone from 25 August to 26 October 2022.Participants The study was conducted among 341 postpartum mothers.Outcome The primary outcome of the study was the magnitude of immediate postpartum anaemia and factors associated with it.Results The magnitude of immediate postpartum anaemia was 28.4% (95% CI (23.5 to 33.3). Factors significantly associated with immediate postpartum anaemia included postpartum haemorrhage (AOR: 4.95; 95% CI 2.09 to 11.76), history of abortion (AOR: 4.01; 95% CI 1.93 to 8.35), rural residence (AOR: 3.03; 95% CI 1.49 to 6.16), poor adherence to iron and folic acid supplementation (AOR: 2.66; 95% CI 1.27 to 5.58) and midupper arm circumference (MUAC) <23 cm (AOR: 2.19; 95% CI 1.08 to 4.42).Conclusion The magnitude of immediate postpartum anaemia was a moderate public health problem. Factors such as postpartum haemorrhage, history of abortion, rural residence, poor adherence to iron and folic acid supplementation and MUAC <23 cm were significantly associated with immediate postpartum anaemia. Strategies should be put in place to encourage early identification and preventive action for the risk factors of immediate postpartum anaemia.